2005
DOI: 10.1590/s0066-782x2005000300010
|View full text |Cite
|
Sign up to set email alerts
|

Monitoração ecocardiográfica da atriosseptostomia com balão

Abstract: ObjectiveTo assess balloon atrial septostomy monitored with echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…As our experience grew, we were able to give up the use of radioscopy and the bedside performance of this procedure became a routine at our service. The large numbers of patients presented in this study shows an effectiveness rate of 96.9% and a low rate of complications (2.0%), represented mainly by arrhythmias associated with the catheter manipulation and that have been previously reported by other authors 14,15 .…”
supporting
confidence: 81%
See 1 more Smart Citation
“…As our experience grew, we were able to give up the use of radioscopy and the bedside performance of this procedure became a routine at our service. The large numbers of patients presented in this study shows an effectiveness rate of 96.9% and a low rate of complications (2.0%), represented mainly by arrhythmias associated with the catheter manipulation and that have been previously reported by other authors 14,15 .…”
supporting
confidence: 81%
“…Following the initial experience of Serra et al 12 in 9 neonates, other national authors reported their experience 13,14 , with the most recent and largest of them being that of de Marchi et al 15 carried out at the Hospital of the School of Medicine of São José do Rio Preto, in 31 neonates with CHD with a low number of complications.…”
mentioning
confidence: 99%
“…Registered complications were of mechanical (e.g., balloon rupture), traumatic (e.g., cardiac damage), embolic (e.g., cerebral event), and electrophysiological (e.g., transient rhythm disorders or AV‐block) nature and were reported for all catheters. The Fogarty and Miller‐Edwards balloon catheters were related with an increased frequency of balloon ruptures, whereas the Z‐5 and Rashkind catheters were not associated with this problem 5,12–14 …”
Section: Resultsmentioning
confidence: 99%
“…Twenty per cent of these children develop heart failure (HF) in the first week of life, 18%, between the first and fourth week and 20% between one and twelve months 5 . The survival rate of children with certain congenital heart defects depends on the presence of a competent interatrial communication 7 .…”
Section: Introductionmentioning
confidence: 99%